الضوابط الفقهية المتعلق بالدائن دراسة تحليلية = The Islamic Jurisprudential principles related to the creditor: an analytical study - Aldosari, Mohammed Benayan; Arif, Arif Ali; Zakariyah, Habeebullah (Al Hikmah Research and Publication Centre, 2023)
This paper aims to gather the Islamic juristic principles with regards to the creditor, linking them to contemporary issues, by putting them into perspectives, consider the most important issues related to the control, and this can only be achieved by using the analytical method in gathering the principles, tracing them to their roots, with evidences and restrictions as well as the opinions of the jurists towards them. The methodology followed therefore was required to be under each principle to clarify its meaning, formulas, study, and contemporary applications. The importance of the study comes in terms of the large number of different issues, and so, it different branches were gathered under one principle in order to facilitate their awareness, and to deduce the legal ruling on them, especially in calamities, where the contemporary applications were mentioned under each principle.